The Columbia Granger's world of poetry 1995. (New York Columbia University Press, 1995)
The Columbia Granger's world of poetry 1995 is a collection of 10,000 public domain poems in full text, 7,500 quotations from poems in copyright all fully searchable by keyword, 135,000 poems in 700 anthologies and 70 collected works indexed by title, first line, author, and subject.
Title from disc label.
Keywords: Poetry